Critical Study of the link between Intellectual property and competition Law, with a focus on the United States, Europe, and India (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This transnational study focuses on the US, Europe, and India to provide a critical evaluation of the global nexus between intellectual property and competition policy. The study's purpose is to look at how these two areas of law interact in order to get a better understanding of how they affect innovation, market competitiveness, and consumer welfare. Intellectual property rights are highlighted for their role in fostering innovation and creativity by providing holders with exclusive rights and monetary incentives. It does, however, recognize that exercising intellectual property rights may result in anti-competitive behaviour, limiting market access and hampering competition. Competition law, on the other hand, is handled as a means of preventing anti-competitive behaviour and guaranteeing fair competition. The goal of competition law is to provide a level playing field for new businesses. However, since IP law and competition law sometimes intersect, the issue of how far IP rights may be exploited without unnecessarily restricting competition arises.